2021
DOI: 10.2147/rrcc.s307151
|View full text |Cite
|
Sign up to set email alerts
|

Recovery Rate and Predictors Among Patients with Acute Coronary Syndrome in Addis Ababa, Ethiopia: A Retrospective Cohort Study

Abstract: Background: Coronary artery disease (CAD) is the leading cause of mortality and morbidity in the world, including Ethiopia. Over seven million people die annually due to acute coronary syndrome (ACS) secondary to CAD. Despite this fact, studies are scant in Ethiopia. Objective: To determine recovery rate and predictors of time to recovery among ACS patients in St. Peter's Specialized Hospital, Addis Ababa, Ethiopia from October 2017 to October 2019. Methodology: A retrospective cohort study was conducted among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…1 According to the risk factors of AMI during our investigation, hypertension (31 (41.2%) patients with STEMI and 14 (66.7%) patients with NSTEMI), diabetes (36 (49.3%) patients with STEMI as well as 11 (45.8%) patients with NSTEMI), and family history of CAD (24 (32.9%) patients of STEMI and 11 (45.8%) patients with STEMI), hyperlipidemia (15 (20.5%) patients with NSTEMI and 6 (25%) patients with STEMI) were the highest prevalence ASCVD risk factors of our study which is compatible with the other studies reported from Greece, India, Ethiopia, Kenya. 13,16,21,22 Moreover, in the present study, a large proportion of STEMI patients were more likely to have a current or previous history of cigarette smoking (39.7%), chat chewing (37%), and coffee drinking (31.5%), but they were less likely to have renal failure and COVID-19 pneumonia which is similar which is similar to previous data reported from Greece and South Trinidad. 13,23 In contrast to our research, data from Ethiopia found that NSTEMI patients had a history of smoking when compared to STEMI patients (64.9% vs 35.1%).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…1 According to the risk factors of AMI during our investigation, hypertension (31 (41.2%) patients with STEMI and 14 (66.7%) patients with NSTEMI), diabetes (36 (49.3%) patients with STEMI as well as 11 (45.8%) patients with NSTEMI), and family history of CAD (24 (32.9%) patients of STEMI and 11 (45.8%) patients with STEMI), hyperlipidemia (15 (20.5%) patients with NSTEMI and 6 (25%) patients with STEMI) were the highest prevalence ASCVD risk factors of our study which is compatible with the other studies reported from Greece, India, Ethiopia, Kenya. 13,16,21,22 Moreover, in the present study, a large proportion of STEMI patients were more likely to have a current or previous history of cigarette smoking (39.7%), chat chewing (37%), and coffee drinking (31.5%), but they were less likely to have renal failure and COVID-19 pneumonia which is similar which is similar to previous data reported from Greece and South Trinidad. 13,23 In contrast to our research, data from Ethiopia found that NSTEMI patients had a history of smoking when compared to STEMI patients (64.9% vs 35.1%).…”
Section: Discussionsupporting
confidence: 90%
“…13 , 23 In contrast to our research, data from Ethiopia found that NSTEMI patients had a history of smoking when compared to STEMI patients (64.9% vs 35.1%). 21 …”
Section: Discussionmentioning
confidence: 99%
“…Yet, these percentages were higher than Ethiopian and Bangladesh studies. 13 , 14 , 20 , 24 , 28 Similarly, 97.5% were on dual antiplatelet aspirin plus clopidogrel or ticagrelor (only in four patients), which was agreed with Iraqi and Bangladesh studies. 14 , 20 The low utilization of ticagrelor might be justified by higher cost, and it is not included in governmental and private insurance in Sudan.…”
Section: Discussionsupporting
confidence: 82%
“…16 In the present study, 99.5% of patients were using statin; this was higher than previously published reports. 13 , 14 , 20 , 24 , 28 Furthermore, ACEIs (or ARBs in cases of intolerance to ACEIs) are recommended in patients with anterior infarction, heart failure with reduced LVEF (<40%), diabetes, or chronic kidney disease (CKD) unless contraindicated in order to reduce cardiovascular mortality and cardiovascular morbidity. 16 In this study, 57.9% of patients were on either ACEIs or ARBs, compared with the literature; it was considered lower than other reports.…”
Section: Discussionmentioning
confidence: 99%
“…In the first, approximately 48% of patients were diagnosed with STEMI, 31% with NSTEMI and 21% with UA [22]. In the study of Tsegaye et al [23], 33% of patients had STEMI, 28% had NSTEMI and 39% had UA. Even in studies involving more than one center, differences are observed.…”
Section: Discussionmentioning
confidence: 97%